(untitled) (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2021)
By observing preschoolers, we can better understand that mathematics is already a part of their surroundings. Research supports that children have an innate sense of pre-mathematical skills that are observed during play. Early Childhood Educators are the bridge between children’s pre-mathematical understanding into informative primary mathematical concepts. Mathematical experiences for children should be built upon play and natural relationships in daily activities. Teachers should design their environments then lesson plan by individualizing math activities and materials in interest areas for open-ended exploration. When educators understand math concepts, they are better able to observe, analyze and evaluate children’s learning and development, and then plan specific individualized activities to foster children’s mathematical progressions.